Understanding Media and Society in the Age of Digitalisation
XV, 256 p. 9 illus.
Keywords: This book provides a selection of international perspectives in the interdisciplinary field of media and communications research with emphasis placed on methodological approaches and new research domains. It includes critical reflections on how to conduct research on digital media culture, especially concerning the potentials and limitations for mixed methods research and online research strategies, as well as a series of hands-on case studies. These range from digital fan cultures, through environmental communication, news media, digital politics during conflicts and crises, to digital media psychology and the emerging field of medical humanities. Diverse in its examples and angles, the book provides a rich snippet of how media research practices are determined by practical factors and research interests. .